FAST ITERATIVE KILOVOLTAGE CONE BEAM TOMOGRAPHY - S. A. Zolotarev; M. A. Mirzavand (Системный анализ и прикладная информатика)
Creating a fast parallel iterative tomographic algorithms based on the use of graphics accelerators, which simultaneously provide the minimization of residual and total variation of the reconstructed image is an important and urgent task, which is of great scientific and practical importance. Such algorithms can be used, for example, in the implementation of radiation therapy patients, because it is always done pre-computed tomography of patients in order to better identify areas which can then be subjected to radiation exposure.